The role of the T‐N tract in advanced stage tongue cancer. Issue 8 (3rd April 2019) - Tagliabue, Marta; Gandini, Sara; Maffini, Fausto; Navach, Valeria; Bruschini, Roberto; Giugliano, Gioacchino; Lombardi, Francesca; Chiocca, Susanna; Rebecchi, Elisabetta; Sica, Eleonora; Tommasino, Massimo; Calabrese, Luca; et al.
Abstract: Background: We investigated the role of the soft tissue tract between the primary tumor and the neck lymph nodes, the "T‐N tract, " in patients with tongue squamous cell carcinoma at an advanced stage. Methods: We performed a compartmental tongue surgery in 233 patients. Cumulative incidence of relapses and overall survival curves were compared by T‐N tract involvement. Multivariate Cox proportional hazards models were used to assess the independent role of T‐N tract. Results: At 4 years of follow‐up, patients with disease in the T‐N tract experienced a significantly more distant recurrence (40%) than did patients without T‐N tract involvement (22%; P = .02). Multivariate Cox models indicate a significant almost triple risk of distant metastases (hazard ratio [HR], 2.70; 95% CI, 1.01‐7.19; P = .05) and double risk of death (HR, 2.09; 95%CI, 1.13‐3.85; P = .02) in patients with "T‐N tract involvement." Conclusions: Our data show that the T‐N tract plays an important role in prognosis and survival in patients with tongue cancer.